2019
DOI: 10.1002/brb3.1207
|View full text |Cite
|
Sign up to set email alerts
|

Altered functional connectivity in binge eating disorder and bulimia nervosa: A resting‐state fMRI study

Abstract: Introduction The etiology of bulimic‐type eating (BTE) disorders such as binge eating disorder (BED) and bulimia nervosa (BN) is still largely unknown. Brain networks subserving the processing of rewards, emotions, and cognitive control seem to play a crucial role in the development and maintenance of eating disorders. Therefore, further investigations into the neurobiological underpinnings are needed to discern abnormal connectivity patterns in BTE disorders. Methods T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 76 publications
3
46
0
Order By: Relevance
“…To date, only 11 studies have examined the relationship between functional network organization and clinical eating phenotypes most typically associated with obesity. Of these, only two studies included individuals with a BMI in the overweight or obese range ( Geliebter et al , 2016 ; Stopyra et al , 2019 ). Further, very little is known about functional network organization in BED, the eating disorder most frequently co-occurring with obesity.…”
Section: Relationship Between Disordered Eating Behaviors and Functiomentioning
confidence: 99%
See 1 more Smart Citation
“…To date, only 11 studies have examined the relationship between functional network organization and clinical eating phenotypes most typically associated with obesity. Of these, only two studies included individuals with a BMI in the overweight or obese range ( Geliebter et al , 2016 ; Stopyra et al , 2019 ). Further, very little is known about functional network organization in BED, the eating disorder most frequently co-occurring with obesity.…”
Section: Relationship Between Disordered Eating Behaviors and Functiomentioning
confidence: 99%
“…This suggests that regions involved in body awareness and sensation might be more integrated in BN, which may be associated with body image distortions and enhanced responsiveness to food cues. Similarly, BED has also been linked to enhanced resting connectivity between regions of somatosensory cortex ( Stopyra et al, 2019 ). Moreover, the strength of connectivity was positively correlated with the frequency of binge episodes ( Stopyra et al, 2019 ), providing evidence that stronger coupling of these regions represents a neural signature of binge eating.…”
Section: Relationship Between Disordered Eating Behaviors and Functiomentioning
confidence: 99%
“…On the other hand, BED showed higher connectivity values in the right cerebellum and right lingual gyrus compared with HC. When comparing BN and BED directly, BED showed a higher connectivity in posterior dorsal cingulate cortex, but lower connectivity in the middle frontal gyrus and angular gyrus (Stopyra et al, 2019). To summarize, BN and BED showed less connectivity in the salience network (aDCC, dACC), higher connectivity in the default mode network, but only in BN (dorsal mPFC, lateral ventral mPFC), and both higher and lower connectivity in the executive network (middle frontal gyrus, angular gyrus, inferior parietal cortex).…”
Section: Functional Connectivitymentioning
confidence: 94%
“…Functional connectivity changes (see Table 1 functional connectivity) largely overlap with the structural connectivity changes discussed above (section 2.2). A large study determining differences in functional connectivity in BED and BN compared with HC (Stopyra et al, 2019) showed lower connectivity in the anterior part of the dorsal cingulate cortex (aDCC), the dorsal part of the anterior cingulate cortex (dACC), and inferior parietal cortex in BED and BN. BED showed lower connectivity within the dorsal medial prefrontal cortex, whilst it was higher in BN compared with HC.…”
Section: Functional Connectivitymentioning
confidence: 99%
“…This approach aims to identify taskindependent and more fundamental functional patterns underlying different states and/or disorders (Fox & Greicius, 2010). RsfMRI has been adopted to describe functional connectivity in relation to eating and weight disorders (García-García et al, 2015;Stopyra et al, 2019), and preliminary evidence converges in identifying altered functional connectivity patterns in regions mainly implicated in impulsivity-related aspects (such as, prefrontal, subcortical and parietal regions) in overeating conditions (García-García et al, 2015;Moreno-Lopez, Contreras-Rodriguez, Soriano-Mas, Stamatakis, & Verdejo-Garcia, 2016;Park, Seo, & Park, 2016). For example, functional connectivity changes within the frontoparietal circuit have been linked to disinhibited eating behavior (as assessed by Three Factor Eating Questionnaire, TFEQ; Stunkard & Messick, 1985) and body mass index (BMI) in normal-and overweight individuals (Park et al, 2016).…”
Section: Resting-state Fmri Investigations Of Binge Eatingmentioning
confidence: 99%